A Method for Bridging the Gap between Business Process Models and Services - Azevedo, Leonardo Guerreiro; Santoro, Flávia; Baião, Fernanda; Diirr, Thaissa; Souza, Alexandre; de Souza, Jairo Francisco; Sousa, Henrique Prado (Histórico da iSys - Brazilian Journal of Information Systems (SERVIDOR ANTIGO - UNIRIO), 2014)
Many proposals in the literature are consensual in making business processes as the starting point of a Service-Oriented system development lifecycle. However, there is no systematic approach that can be easily applied in practice. We argue that an effective SOA approach requires an integrated view of organizational business processes, where services are explicitly related to business models components. Accomplishing these requirements is vital for bridging the gap between business needs and their supporting services. This work proposes a top-down method for service identification and analysis from business process models. Each step of the method implements a set of heuristics that are also specified. The method is presented in detail, and constitutes a systematic guide for service identification and analysis. A case study is conducted to demonstrate the use of the method in practice.